Pengaruh Kelekatan Anak dengan Orang Tua Terhadap Kecenderungan Gelotophobia - Felicia Gabriela Utomo; Maria Goretti Adiyanti (Bulletin of Counseling and Psychotherapy, 2022)
Gelotophobia is the fear of someone being laughed at or looking ridiculous in the eyes of others which can cause the individual to withdraw from the surrounding environment and experience symptoms such as palpitations, shaking, shortness of breath, difficulty speaking, or even no expression at all which begins in childhood as a child as a result of the failed relationship between the baby and his caregiver. These traumatic events are repeated because of being laughed at and ridiculed so that the bond between the child and his parents is not strong. This affects the emergence of gelotophobia in children, especially if the parents do not show affection and warmth. This study aims to determine the effect of parental attachment on the tendency of gelotophobia among children aged 16-18 years in Indonesia. This research uses a quantitative method with simple linear regression data analysis. The participants in this study were 443 people selected using a purposive sampling technique. Data collection using the Inventory of Parent and Peer Attachment (IPPA) instrument and the GELOPH-15 scale modified by the researcher and collected by questionnaires. The results showed a significant effect of parental attachment on the tendency of gelotophobia.